2021
DOI: 10.1080/00325899.2021.1909212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light (X = Mg, Si) and heavy (X = Zn) metals on the microstructural evolution and densification of AlCuFeMnTi-X high-entropy alloy processed by advanced powder metallurgy

Abstract: Novel AlCuFeMnTi-X high-entropy alloy (HEA) powder mixture with individual X = Mg, Si, Zn was mechanically alloyed for 45 h and consolidated at 700°C by spark plasma sintering (SPS). The effect of the addition of Mg, Si and Zn was studied on the microstructural evolution, density and microhardness of the developed HEAs. The results demonstrated that milled HEAs were body-centered cubic (BCC) structured (BCC1 and BCC2). The BCC2 fraction was highest in AlCuFeMnTi-Zn followed by AlCuFeMnTi-Si. However, minor Ti,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Similarly, the brittle nature of BCC HEAs hinders their application in load-bearing safety structures. To overcome these drawbacks, versatile combinations of HEAs have been proposed in the existing literature [6][7][8][9]. Nevertheless, owing to their exceptional mechanical performance and thermomechanical stability, HEAs are employed in various applications, including in nuclear reactors, spacecraft components and additive manufacturing, and have attracted significant research [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the brittle nature of BCC HEAs hinders their application in load-bearing safety structures. To overcome these drawbacks, versatile combinations of HEAs have been proposed in the existing literature [6][7][8][9]. Nevertheless, owing to their exceptional mechanical performance and thermomechanical stability, HEAs are employed in various applications, including in nuclear reactors, spacecraft components and additive manufacturing, and have attracted significant research [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the effects of the addition of metallic elements on the mechanical performance of HEAs. For example, some studies have added minute Si fractions to HEAs for automotive structural applications [7,26,27]. However, despite their many benefits, the development of robust HEAs for automotive structural parts, which can replace the Al–Si–Cu alloys, is still in its early stages, and further research is required to fully understand their properties and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al suggested dual-phase FCC+BCC non-Cantor AlCuSiFeZn HEA balance the strength and ductility of the HEAs [13]. Likewise, Chae et al produced AlCuFeMgMnTi and AlCuFeMnTiSi HEAs to improve the strength-to-density ratio for lightweight automotive applications [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al studied the impact of V and Mn doping on the mechanical and wear properties of CoCrFeNi HEA and discovered that doping with V significantly reinforced the alloy and improved wear behaviour by three times compared to CoCrFeNiMn owing to the inherent σ-solid phase [28]. Few studies have also explored the impact of semimetals like Si on HEAs [14,29]. Likewise, the addition of Cu is necessary to improve the wear resistance and lubrication of HEAs in automotive pistons which are subjected to continuous reciprocating wear [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers also produced a lightweight Al 20 Be 20 Fe 10 Si 15 Ti 35 HEA by casting with a density of 3.91 g/cm 3 and hardness of −911 HV [17]. However, most of the lightweight HEAs contain toxic, expensive, and scarce elements [18][19][20]. Various strengthening mechanisms, such as solid-solution hardening, grain refinement, precipitation hardening, and heterogeneous structure hardening, have been recommended to balance strength and plasticity Materials 2021, 14, 4945 2 of 13 in the existing HEAs [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%